Ultrastructural features of the double capsulated connective tissue around silicone prostheses. Issue 6 (10th December 2020) - Calderan, Laura; Panettiere, Pietro; Accorsi, Danilo; Marchi, Alessandra; Bernardi, Paolo; Benati, Donatella; Conti, Giamaica; Chirumbolo, Salvatore; Zingaretti, Nicola; Parodi, Pier Camillo; Cisterna, Barbara; Sbarbati, Andrea
Abstract: The implantation of breast prostheses for both aesthetic and reconstructive purposes has been growing exponentially in the last 20 years. Safety and prosthesis lifespan are majorly debated issues in relation to the correlated long‐term complications. Mainly the periprosthetic capsule that develops around the implant is often the cause of complications and particularly for macrotextured silicone breast implants. Some reports have tried to elucidate the mechanism by which macrotextured silicone implants undergo damage and cause double capsule formation. In this study, we investigated the morphological characteristics of double capsule of macrotextured implants surgically removed from patients. With the use of microscopy techniques, this work analyzed the newly formed tissue observed in the interaction between synthetic and biological surfaces. Abstract : Macrotextured silicon prosthesis used for reconstructive medicine promote formation of double capsule. The double capsule show different tissue organizations. Fragments of silicon material are embedded in the tissue and may be a concause of the double‐capsule formation.